KAJIAN ESTETIKA ORNAMEN PADA ELEMEN MASJID AGUNG SURAKARTA DALAM KONTEKS BUDAYA - Yunianti, Esterica (Badan Pengembang Konservasi UNNES, 2018)
Ornaments of the Great Mosque of Surakarta appear in several forms. Ornaments influenced by Hindu, Buddhist, Islamic and Javanese patterns are interesting phenomena to be studied. This study aims to (1) Identify and analyze ornaments (2) Analyze the meaning of ornaments (3) Analyze the linkages of aesthetic elements found in the ornaments of Surakarta Grand Mosque with education. This study uses qualitative methods through aesthetic studies to find the shape and meaning of ornaments in the Great Mosque of Surakarta. Data collection is done by (1) Observation (2) Interview (3) Study of documents. Data analysis is done by data reduction, data presentation, and conclusion drawing / verification. Results (1) ornaments on elements of the Great Mosque of Surakarta have a visual form that is influenced by Javanese culture, Islam is related to Hindu-Buddhism (2) ornaments on elements of the Great Mosque of Surakarta have aesthetic values that are in accordance with 'the concepts of Javanese aesthetics and Islamic aesthetics (3 ) ornaments on elements of the Great Mosque of Surakarta have educational values including useful and valuable values (truth values), beautiful (aesthetic values), good (moral values), religious (religious values).